Śrīmadbhāgavata pātrānukramaṇikā evaṃ sthānānukramaṇikā - Caturvedī, Vāsudevakrshṇa, 1934- (Śrīkrshṇa Satsaṅga Bhavana Prakāśana : Prāptisthāna Bajaraṅga Pustakālaya, 1982)
Index of proper name sin the Bhāgavatapurāṇa, Hindu mythological text.